Cryptic diversity and phylogeographic patterns of Deto echinata (Isopoda: Detonidae) in southern Africa - Santamaria, Carlos A.; Griffiths, Charles L. (PeerJ, 2023)
Recent phylogeographic studies of poorly-dispersing coastal invertebrates in highly biodiverse regions have led to the discovery of high levels of cryptic diversity and complex phylogeographic patterns that suggest isolation, geological, and ecological processes have shaped their biodiversity. Studies of southern African coastal invertebrates have uncovered cryptic diversity for various taxa and phylogeographic patterns that, although sharing some similarities across taxa, do differ. These findings underscore the need for additional studies to better understand the biodiversity levels, distributional patterns, and processes responsible for producing coastal biodiversity in that region. The coastal isopod Deto echinata is of particular interest, as its complex taxonomic history, poor dispersal capabilities, and broad geographic distribution suggest the potential for cryptic diversity. We use mitochondrial and nuclear sequences to characterize D. echinata individuals from localities ranging from northern Namibia to Glentana, about 2,500 km along the coastline on the south coast of South Africa. These are used to assess whether D. echinata harbors cryptic genetic diversity and whether phylogeographic distributional patterns correlate with those previously documented for other coastal isopods in the region. Analysis of mitochondrial and nuclear sequences revealed two deeply-divergent lineages that exhibit a distributional break in the Cape Peninsula region. These findings suggest D. echinata is a cryptic species complex in need of taxonomic revision and highlight the need for further taxonomic and phylogeographic studies of similarly poorly-dispersing coastal invertebrates in southern Africa.
Keywords: Biodiversity; Biogeography; Oniscidea; Isopoda; Intertidal; Vicariance